ANALYSIS OF GUBETAN (GUNUNG BERAPI BUATAN) TEACHING MATERIALS ON ONLINE LISTENING SKILLS - Alika Dwi Septiani; Aulia Diva Dry Anindia; Sabila Fitriani; Yuni Ertinawati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research analyzes students' listening skills in online learning by using GUBETAN (Gunung Berapi Buatan) teaching materials. The aim is to evaluate the effectiveness of this method in improving students' listening skills. The methods used are demonstration, question and answer and data analysis methods. Learning activities are carried out through the Google Meet application and evaluation using Quizizz. The results showed that this online GUBETAN listening activity was less feasible because many students experienced obstacles.